2010
DOI: 10.1038/ejcn.2010.123
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain fatty acids and commensal microbiota in the faeces of severely malnourished children with cholera rehydrated with three different carbohydrates

Abstract: Background: Short-chain fatty acids (SCFAs) liberated by fermentation of complex carbohydrates might stimulate water and salt absorption, and provide energy. The aim of the study was to assess the number and proportion of faecal bacteria and the concentration of SCFAs of severely malnourished children with cholera receiving oral rehydration solution (ORS) containing glucose, amylase-resistant starch (ARS) or rice. Methods: Serial faecal samples were collected from 30 malnourished children with cholera until re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 43 publications
2
17
0
1
Order By: Relevance
“…The idea is that, it is easier for mother to remember any event of illness of her child within this time period. Again, in our previous study we observed that malnourished children with cholera who received antibiotics, resume their gut microbiota proportion upto the level of malnourished children (without cholera) after 1 month (Monira et al, 2010). At the same time this study has limitations that it could not collect and analyze large number of samples covering a wide range of people of various socioeconomic status and areas of Bangladesh.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The idea is that, it is easier for mother to remember any event of illness of her child within this time period. Again, in our previous study we observed that malnourished children with cholera who received antibiotics, resume their gut microbiota proportion upto the level of malnourished children (without cholera) after 1 month (Monira et al, 2010). At the same time this study has limitations that it could not collect and analyze large number of samples covering a wide range of people of various socioeconomic status and areas of Bangladesh.…”
Section: Discussionmentioning
confidence: 81%
“…Pathogenic bacteria can alter the gut microbiota proportion significantly. Namely, colonization of Vibrio cholerae in the gut epithelial cells causes profuse loss of water and electrolytes which results in expulsion of Bifidobacteria and invites increasing proportion of Enterobacteriaceae (Monira et al, 2010). Role of gut microbiota in immune diseases has been demonstrated and bacterial imbalance has been associated with pathologies such as inflammatory bowel disease and obesity (Ley et al, 2006; Marteau et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the regulon of CrbS is highly expressed in the terminal ileum of both humans and infant mice, suggesting that the acetate switch may be thrown in this environment (Lombardo et al, 2007; Mandlik et al, 2011; Osorio et al, 2005). As further evidence of this, clinical studies show that SCFA are depleted in the stool of patients suffering from cholera and that the reappearance of SCFA is associated with recovery (Monira et al, 2010). These observations suggest that the pathway by which V. cholerae controls host metabolism in Drosophila is intact in the mammalian intestine and possibly active in cholera.…”
Section: Discussionmentioning
confidence: 98%
“…Earlier reports are not consistent on this point; poor nutritional status has been associated with lower levels of faecal lactobacilli [19] or no difference in number of colonised subjects. [20] While the previous studies relied on culturing or used fluorescent in situ hybridisation (FISH), the present study relied on quantitative real time PCR; it is possible that this has contributed to the difference. However, it is likely to relate to the study population; as we reported earlier the faecal Lactobacillus levels were exceptionally high in this population.…”
Section: Discussionmentioning
confidence: 99%